a)(-1,5)³+[1,(6)]²=(-15/10)³+(15/9)²=(-3/2)³+(5/3)²=
=-27/8+25/9=(-243+200)/72=-43/72=-0,597(2)
b) (0,5)³-[-1,(3)]²=(1/2)³-(-12/9)²=1/8-(-4/3)²=1/8-16/9=(9-128)/72=-119/72=
=-1,652(7)
c)[0,8(3)]²-(0,5)³=(5/6)²-(1/2)³=25/36-1/8=(50-9)/72=41/72=0,569(4)
0,8(3)=(83-8)/90=75/90=5/6
d) [-0,1(6)]²-(-1,5)²=(-1/6)²-(-3/2)²=1/36-9/4=1/36-81/36=-80/36=-2(2)
e)[1,(3)]²+[-0,(6)]³=(12/9)²+(-6/9)³=(4/3)²+(-2/3)³=16/9-8/27=48/27-8/27=
=40/27=1,(481)
f)[-0,(3)]³-[0,1(6)]²
=(-1/3)³-(1/6)²
=(-1/27)-(1/36)
=-4/108-3/108=-7/108=
=-0,06(481)